WIFI SCANNER FOR OBTAINING PEDESTRIAN DATA - Arief Hidayat; Shintaro Terabe; Hideki Yaginuma (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2017)
Recently, many technologies to estimate pedestrian data to know about pedestrian travel behavior. Wifi is one of the most useful technologies that can be used in counting pedestrian data. This paper described using of WiFi scanner which carried out seven times circulated the bus. The method used WiFi and GPS are to counting MAC address as raw data from pedestrian smartphone or WiFi devices nearfrom the bus as long as the bus going around the route, generate and processing to be pedestrian data. There are five processes to make pedestrian data from raw data. The purpose of this study is to calculate, obtain and estimate the number of pedestrian data divide circulation number and road segmentation.